O negócio por trás do modelo de regulação fundiária: o caso de Cariacica (ES) - Vieira, Marissol Silva (2019)
With the predominantly urban population, made up of migrants who sought the cities of the current Greater Vitória Metropolitan Region - RMGV / ES, especially from the 1960s, due to the land disruption of the countryside combined with the political-economic transformations of these cities, Cariacica, municipality of the Metropolitan Region and spatial outline of this study, suffered from the impacts of irregular and unequal occupation of space caused by this migration. Recently land regularization has stood out among the municipal urban public policies that aim to solve the problem of irregular settlements, as in the Bela Vista and Castelo Branco neighborhoods, studied by this work. This dissertation aims to raise possible implications and consequences of the land regularization format applied in Cariacica, using for this bibliographic review and investigation through empirical research. This regularization format, motivated and implemented by the private sector, is being promoted without compromise with urban planning, housing or municipal social public policies, with little or no regulation or participation by the government in decisions, due to its limitations and interests. several. The starting point for the study was the hypothesis that the real interest in the regularization of these communities is to absorb a new market niche of architectural and engineering projects, since the municipality cannot meet this demand. However, this model of regularization may have unintended consequences, such as the release of these properties and their reintegration into the logic of capital reproduction that, in the case of the Bela Vista and Castelo Branco neighborhoods, located in central and privileged areas of the municipality, comes become interesting to the real estate market, suppressing part of the social obligations necessary to improve the quality of life of the population.